Vitrine 98. (Antwerpen : Flanders Fashion Institute, 1998)
Figus, Angelo ; Heylen, Anna ; Lacres, Eva ; Simons, Raf ; Demeulemeester, Ann ; Grognard, Inge ; Stoops, Ronald ; Persoons, Jurgi ; Van Assche, Kris ; Resend's, Anne Sophie De Campos ; Strasser, Markus ; Van Noten, Dries ; Branquinho, Veronique ; Lerch, Carolin ; Neels, Wim ; Mees, Emmy ; Bonne, Lieven ; Pieters, Bruno ; Vandevorst, A.F. ; Schneider, Stephan ; Margiela, Martin ; Van Gorp, Lieve ; Van Steenbergen, Tim ; De Backer, Bart ; Loh, Anke ; Bikkenbergs, Dirk ; Wijnants, Christian ; Van Beirendonck, Walter ; Van Saene, Dirk ; Boudens, Paul
Nederlands
boek